2021
DOI: 10.3389/fcvm.2021.764831
|View full text |Cite
|
Sign up to set email alerts
|

miR-153-3p Targets βII Spectrin to Regulate Formaldehyde-Induced Cardiomyocyte Apoptosis

Abstract: Background: Formaldehyde (FA) is ubiquitous in the environment and can be transferred to the fetus through placental circulation, causing miscarriage and congenital heart disease (CHD). Studies have shown that βII spectrin is necessary for cardiomyocyte survival and differentiation, and its loss leads to heart development defects and cardiomyocyte apoptosis. Additionally, previous studies have demonstrated that miRNA is essential in heart development and remodeling. However, whether miRNA regulates FA-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Specifically, in cardiac diseases, it has been found that miR-153-3p contributes to mitochondrial fragmentation in cardiac hypertrophy [ 9 ]. The regulatory influence of miR-153-3p on cardiomyocyte apoptosis by directly targeting β II spectrin has also been uncovered [ 14 ]. Recent evidence has also pointed out that miR-153-3p is able to affect cardiomyocyte apoptosis induced by formaldehyde [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in cardiac diseases, it has been found that miR-153-3p contributes to mitochondrial fragmentation in cardiac hypertrophy [ 9 ]. The regulatory influence of miR-153-3p on cardiomyocyte apoptosis by directly targeting β II spectrin has also been uncovered [ 14 ]. Recent evidence has also pointed out that miR-153-3p is able to affect cardiomyocyte apoptosis induced by formaldehyde [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory influence of miR-153-3p on cardiomyocyte apoptosis by directly targeting β II spectrin has also been uncovered [ 14 ]. Recent evidence has also pointed out that miR-153-3p is able to affect cardiomyocyte apoptosis induced by formaldehyde [ 14 ]. Herein, we aim to figure out whether miR-153-3p is a participant of the Gm15834-centered ceRNA regulatory axis.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the TUNEL‐positive cells we quantified corroborated the significant increase during MRLC RNAi knockdown (Figure 5B ). We quantified the expression levels of caspase‐2 , 48 caspase‐7 , 49 the pro‐apoptotic gene bak 50 and antiapoptotic gene Bcl‐2 , 51 which are reported to be involved in apoptosis. qPCR quantification showed their upregulation in MRLC RNAi animals ( n = 30 animals; Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…The cells stained with TUNEL (TdT-mediated dUTP nick-end labeling) were considered apoptotic. The total number of apoptotic cells was calculated using DAPI (2-(4-amidinophenyl)-6-indolecarbamidine dihydrochloride) staining [ 19 ].…”
Section: Methodsmentioning
confidence: 99%